B-type natriuretic peptide levels in patients with pericardial effusion undergoing pericardiocentesis. (1st June 2016) - Lauri, Gianfranco; Rossi, Chiara; Rubino, Mara; Cosentino, Nicola; Milazzo, Valentina; Marana, Ivana; Cabiati, Angelo; Moltrasio, Marco; De Metrio, Monica; Grazi, Marco; Campodonico, Jeness; Assanelli, Emilio; et al.
Abstract: Objectives: Pericardial effusion is characterized by progressive accumulation of fluid within the pericardial space, resulting in increased intra-pericardial pressure and compression of the heart. As B-type natriuretic peptide (BNP) is secreted by the ventricles in response to increased myocardial stretch, we hypothesized that pericardial effusion, as well as its resolution, might influence BNP plasma levels. Methods: We prospectively measured, in 146 consecutive patients with pericardial effusion, BNP plasma levels at baseline, soon after, and 24 h after pericardiocentesis. A scoring system based on 7 clinical and echocardiographic parameters was developed, and patients were classified according to the number of variables as having low (0–2), intermediate (3–4), or high (5–7) severity score. Results: Out of the 146 patients, 42 (29%) had normal values (< 100 pg/ml), whereas 104 (71%) had high BNP values at baseline. In the whole population, baseline BNP levels significantly decreased as the severity score increased (r = − 0.21; P = 0.01). 24 h after pericardiocentesis, a significant increase in BNP was observed in patients with intermediate (P = 0.004) score and with high (P < 0.001) severity score; no increase occurred in low score patients (P = 0.56). The higher was the severity score, the steeper was the increase in BNP through the three time-points considered (P = 0.04). Conclusions: The results of the present study show that BNP plasma levels are suppressed in the presence of severe pericardial effusion, and that they rise after pericardiocentesis. Future studies should investigate the role of BNP in assisting clinicians in the decision-making process of pericardial fluid drainage.